Influence of Dietary Phosphorus and Zinc Levels on Whole Body Mineral, Liver Mineral, and Liver Vitamin-C Contents of Fingerling Rainbow Trout, Oncorhynchus mykiss (Journal of Agriculture & Rural Development, 2008)
A laboratory based 2 Ã 2 factorial experiment was conducted to investigate the influence of dietary phosphorus and zinc levels on whole body mineral, liver mineral, and liver vitamin-C contents of fingerling rainbow trout for 21 weeks. Two levels of phosphorus (19 and 30 mg g-1) and two levels of zinc (55 and 100 Î¼ g g-1) in the dry diets were tested. Duplicate tanks of 30 rainbow trout (average weight 1.56 Â± 0.24 g) per 60L glass tank were fed experimental diets three times a day to satiation level in 15 to 24oC water temperature. The result of the present study demonstrated that dietary zinc supplementation significantly influenced the whole body zinc and liver copper contents in fingerling rainbow trout where as additional phosphorus did not show any significant difference. Zinc supplementation significantly influenced the liver vitamin-C contents of the fish. Hence it is clear that zinc supplementation is necessary in fingerling rainbow trout feed. Further studies in this area are needed broadly. Key words: Phosphorus, zinc, whole body, liver mineral, liver vitamin-C, rainbow trout DOI = 10.3329/jard.v5i1.1470 J Agric Rural Dev 5(1&2), 135-142, June 2007